ARSITEKTUR STASIUN LASEM DITINJAU DARI PENDEKATAN ARKEOLOGI KESEJARAHAN - Candrika Ilham Wijaya (AMERTA, 2023)
Abstract. Lasem Station Architecture Viewed from Historical Archaeological Approach. At the end of the 19th century, Lasem Station was built by the Semarang-Joana Stoomtram Maatschappij (SJS) as a railway line connecting Semarang and Lasem. Despite existing studies pertaining to Lasem, research on the specific architecture of the Lasem Station remains limited. Through a historical archaeological approach, this investigation seeks to dissect fundamental elements such as the physical form, architectural style, and the social and cultural background of the construction of Lasem Station during the colonial era. Data were procured through field observations, archival document analysis (including historical documents, old maps, and photographs from that era), interviews, and relevant secondary references. The research findings indicate that the Lasem Station played a vital role in connecting the production sector with the trading center, facilitating the conveyance of commodities such as teak wood, tobacco, and sugar from inland regions to the coastal area, thereby establishing the station as a centre of distribution and economic activity within the city of Lasem. This research also sheds light on the relocation of the station’s position westward of Lasem City, which improved the distribution of goods and railway maintenance. The Lasem Station, as a historical legacy of SJS, boasts a grand colonial architectural style, characterized by curved ornamentation above Romanesque-style doors, the use of wide windows and doors, and a gabled roof design. Despite experiencing modifications primarily in the canopy, the original elements, such as floors, walls, and roofs, have been preserved, maintaining their authenticity. Overall, this study unveils the role of the railway route and spatial arrangement of the Lasem Station in reshaping the economic dynamics and urban structure, while the architecture of Lasem Station reflects a rich cultural and historical heritage. These architectural elements can reflects the colonial influence and the socio-economic dynamics of the era. Keyword: Lasem Station, Historical Archaeology, Semarang Joana Stoomtram Maatschappij   Abstrak. Pada akhir abad 19, Stasiun Lasem dibangun oleh Semarang-Joana Stoomtram Maatschappij (SJS) sebagai jalur yang menghubungkan antara Semarang dan Lasem. Kajian tentang Lasem sudah banyak dilakukan, akan tetapi penelitian arsitektur khusus Stasiun Lasem masih terbatas. Melalui pendekatan arkeologi kesejarahan, penelitian ini berupaya mengurai elemen-elemen fundamental, seperti bentuk fisik, gaya arsitektur, serta latar belakang sosial dan budaya dalam pembangunan Stasiun Lasem pada era kolonial. Data diperoleh melalui observasi lapangan, analisis dokumen arsip (termasuk dokumen sejarah, peta lama, dan fotografi era tersebut), wawancara, dan referensi sekunder yang relevan. Hasil penelitian menunjukkan bahwa Stasiun Lasem memainkan peran vital dalam menghubungkan sektor produksi dengan pusat perdagangan, memudahkan komoditas, seperti kayu jati, tembakau, dan gula dipindahkan dari pedalaman menuju pesisir, dan menjadikan stasiun tersebut sebagai pusat distribusi dan aktivitas ekonomi di Kota Lasem. Penelitian ini juga menyoroti perpindahan posisi stasiun ke barat Kota Lasem yang memperlancar distribusi barang dan pemeliharaan rel kereta api. Stasiun Lasem, sebagai peninggalan sejarah SJS memiliki gaya arsitektur kolonial yang megah dengan ornamentasi lengkung di atas pintu berlanggam romawi, penggunaan jendela dan pintu yang lebar, serta gaya atap dengan tipe gables. Meskipun mengalami modifikasi terutama kanopi, elemen-elemen asli seperti lantai, dinding, dan atap tetap terjaga, sehingga masih terlihat keasliannya. Secara keseluruhan, penelitian ini mengungkapkan peran jalur kereta api dan tata letak Stasiun Lasem dalam mengubah dinamika ekonomi dan struktur kota, sementara arsitektur Stasiun Lasem merefleksikan warisan budaya dan sejarah yang kaya. Elemen-elemen arsitektural tersebut dapat mencerminkan pengaruh kolonial dan dinamika sosial ekonomi pada periode tersebut.   Kata kunci: Stasiun Lasem, Arkeologi Kesejarahan, Semarang Joana Stoomtram Maatschappij